2014
DOI: 10.1007/s00701-014-2165-y
|View full text |Cite
|
Sign up to set email alerts
|

Flow-related intracranial aneurysms associated with unfused arterial twigs relevant to different vascular anomalies: embryologic and hemodynamic considerations

Abstract: These unique vascular anomalies, T-MCA and T-NACA, which are caused by heterogeneous maldevelopment of the primitive cerebral vessels, are not benign because of their frequent association with flow-related aneurysms, which are vulnerable to rupture. Microsurgical or endovascular treatments for this type of flow-related aneurysm associated with twigs are mandatory to prevent fatal rebleeding, and more attention has to be given when physicians encounter steno-occlusive MCA lesions in patients with subarachnoid h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
59
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(60 citation statements)
references
References 11 publications
0
59
1
Order By: Relevance
“…Shin et al argued that rete MCA anomalies were not an acquired disease because they were identified at a relatively young age (average age 41 years), and patients had neither obvious atherosclerotic degeneration nor leptomeningeal collaterals on cerebral angiography. 26 In a pooled analysis including our cases, patients were not relatively young (average age 51.2 years). Furthermore, the whitish vessel of the rete MCA anomalies found in our operative cases was different from the usual atherosclerotic stenoocclusive vessel.…”
Section: Pathogenesis (Congenital Versus Acquired)mentioning
confidence: 81%
See 2 more Smart Citations
“…Shin et al argued that rete MCA anomalies were not an acquired disease because they were identified at a relatively young age (average age 41 years), and patients had neither obvious atherosclerotic degeneration nor leptomeningeal collaterals on cerebral angiography. 26 In a pooled analysis including our cases, patients were not relatively young (average age 51.2 years). Furthermore, the whitish vessel of the rete MCA anomalies found in our operative cases was different from the usual atherosclerotic stenoocclusive vessel.…”
Section: Pathogenesis (Congenital Versus Acquired)mentioning
confidence: 81%
“…Many of these papers were published in Asia, including South Korea and Japan. 2,5,[8][9][10]12,14,16,18,19,21,[24][25][26][27][28][29][30] Therefore, for the clarity of these anomalies, we have coined the term "rete MCA anomaly" to integrate these various names. Rete means a network of blood vessels.…”
Section: Various Namesmentioning
confidence: 99%
See 1 more Smart Citation
“…At last Shin et al [18] reported four cases with flow related six aneurysms in the twig-like segments. The author named one of these cases as twig-like MCA and the other three of them as twig-like networks of an anomalous collateral artery.…”
Section: Discussionmentioning
confidence: 97%
“…8) In 2012, Seo et al reported the largest series with 15 cases and named the finding as aplastic or twig-like MCA. 10) Recently, Shin et al reported four cases, 11) and Akkan et al reported six cases. 12) Common angiographical features of these cases were as follows; 1) a steno-occlusive lesion can be seen on the unilateral MCA, 2) plexiform arterial network exists instead of the main MCA trunk, 3) perforators arise from the plexiform arterial network, and 4) cortical branches beyond the occluded MCA trunk have anterograde flow with normal configuration.…”
Section: Anomalies Of the Mcamentioning
confidence: 99%